2019
DOI: 10.3389/fnins.2019.00414
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sigma Receptors With Afobazole Modulates Microglial, but Not Neuronal, Apoptotic Gene Expression in Response to Long-Term Ischemia Exposure

Abstract: Stroke continues to be a leading cause of death and serious long-term disability. The lack of therapeutic options for treating stroke at delayed time points (≥6 h post-stroke) remains a challenge. The sigma receptor agonist, afobazole, an anxiolytic used clinically in Russia, has been shown to reduce neuronal and glial cell injury following ischemia and acidosis; both of which have been shown to play important roles following an ischemic stroke. However, the mechanism(s) responsible for this cytoprotection rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the inhibition of GSK3β and CDK/p25 by AF710B, upon interaction with both M1 and σ 1 receptors, results as a promising approach in the treatment of tauopathies [82]. The effect of σ 1 receptors in inflammation through microglia modulation has been reported [54,86,87], and AF710B was shown to reduce reactive astrocytes and activated microglia in the animals, as detected by the low levels of glial fibrillary acidic protein (GFAP) and ionized calcium-binding adapter molecule 1 (Iba-1). Notably, astrocytes and microglia are increased in number and size in AD patients.…”
Section: Mtdls Acting At σ 1 Receptor and Cholinergic Systemmentioning
confidence: 99%
“…Therefore, the inhibition of GSK3β and CDK/p25 by AF710B, upon interaction with both M1 and σ 1 receptors, results as a promising approach in the treatment of tauopathies [82]. The effect of σ 1 receptors in inflammation through microglia modulation has been reported [54,86,87], and AF710B was shown to reduce reactive astrocytes and activated microglia in the animals, as detected by the low levels of glial fibrillary acidic protein (GFAP) and ionized calcium-binding adapter molecule 1 (Iba-1). Notably, astrocytes and microglia are increased in number and size in AD patients.…”
Section: Mtdls Acting At σ 1 Receptor and Cholinergic Systemmentioning
confidence: 99%
“…The anxiolytic afobazole, a Sigma1R ligand with agonist-like actions [269,366,367], introduced into medical practice in Russia, exhibits cytoprotective and neuroprotective properties in a number of experimental models [368][369][370][371][372][373][374][375][376][377][378][379][380] (Table S1).…”
Section: Features Of the Neuroprotective Action Of Sigma1r Ligandsmentioning
confidence: 99%
“… 2 , 3 The sigma receptor has been of interest since its discovery due to its wide range of biological functions, and it is considered to play significant roles in regulating cell survival, morphology and differentiation. 4 , 5 It has gradually become a target for cancer diagnosis and treatment. 6 , 7 , 8 , 9 The sigma‐2 receptor is an 18–21 kD membrane protein, 2 and recent receptor‐ligand binding assays have shown that it is highly expressed in the liver and kidney of rabbits.…”
Section: Introductionmentioning
confidence: 99%